2016
DOI: 10.1038/nature17439
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning-assisted materials discovery using failed experiments

Abstract: Inorganic-organic hybrid materials such as organically templated metal oxides, metal-organic frameworks (MOFs) and organohalide perovskites have been studied for decades, and hydrothermal and (non-aqueous) solvothermal syntheses have produced thousands of new materials that collectively contain nearly all the metals in the periodic table. Nevertheless, the formation of these compounds is not fully understood, and development of new compounds relies primarily on exploratory syntheses. Simulation- and data-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
935
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,302 publications
(999 citation statements)
references
References 34 publications
3
935
0
14
Order By: Relevance
“…The Dark Reactions data shows different top ranked features for the three models, though all three rankings include the minimum Pauling electronegativity and the maximum Pearson electronegativity in the top ranked cluster of features. These values are calculated for the inorganic components of the reaction and have been shown to be important for distinguishing between chemical systems in this data set [20], which this audit confirms. Features indicating the presence of elements and amounts of metal elements with specific valence counts similarly allow the models to classify chemical systems.…”
Section: A Black-box Feature Auditingmentioning
confidence: 56%
See 2 more Smart Citations
“…The Dark Reactions data shows different top ranked features for the three models, though all three rankings include the minimum Pauling electronegativity and the maximum Pearson electronegativity in the top ranked cluster of features. These values are calculated for the inorganic components of the reaction and have been shown to be important for distinguishing between chemical systems in this data set [20], which this audit confirms. Features indicating the presence of elements and amounts of metal elements with specific valence counts similarly allow the models to classify chemical systems.…”
Section: A Black-box Feature Auditingmentioning
confidence: 56%
“…The SVM and FNN top features include atomic properties of the inorganics that are related to the electronegativity of an element, so these proxies are correctly also highly ranked. The top ranked decision tree features additionally include the average molecular polarizability for the organic components, which was previously hypothesized as important to synthesis of templated vanadium selenites explored via this data set [20]. For all three models, the lowest ranked descriptors are constants scored correctly as having no influence to the model.…”
Section: A Black-box Feature Auditingmentioning
confidence: 99%
See 1 more Smart Citation
“…if we are given a structure, can we predict its performance, say in CO 2 separations, based on its surface area, pore size, or pore volume? There have been several recent studies dedicated to answering this question using models developed by machine learning 32,45,114,[131][132][133][134] , a field that is becoming extremely powerful in materials science 135,136 . It was shown that 1-dimensional geometric descriptors are able to successfully predict adsorption at high pressures 134,137 and low temperatures 114 , using representative datasets of materials to train machine learning models.…”
Section: H1 Data Mining Approachesmentioning
confidence: 99%
“…[5] Fore xample,r ecently,W icker and Cooper [6] applied machine learning methods to draw am ap of crystallinity according to the size of am olecule and its number of rotatable bonds.S imilarly,O liynyk et al [7] used machine learning to predict structures of inorganic binary compounds of the general formula AB by considering various atomic and physical properties in their calculations.O f particular interest, Norquist et al [8] made use of data from unsuccessful syntheses to predict reaction outcomes of vanadium compounds and compared the efficiencyo ft heir algorithms with the typical strategies that human chemists apply.…”
mentioning
confidence: 99%